Penerapan Media Pembelajaran di Sekolah Praktek: (Studi Kasus pada Mahasiswa FKIP UMMY Solok yang Praktek Lapangan Kependidikan (PLK) Semester Ganjil 2013/2014) - Perta, Nona; Afrahamiryano, Afrahamiryano; Ariani, Dewi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2016)
The background of this research come from of the result of research faculty beginners which have been raised in 2011 by title “The Evaluation of Learning Method in Education Media Subject at FKIP UMMY”. Based on that result, researcher interest to develop research about how applying of instructional media in school practice by student field practice of FKIP. This type of the research is qualitative research. Means of collecting data in this researchis the researchers them selves and the team, and comes with interview, observation guidelines, and documentation to assure the validity ofthe dataisbased on standardsof credibility as the standard fit and easier to analyze that data and research would be moreaccurate. Guarantor ofthe validity ofthe datais done byan extension ofthe standardof participation, a more diligen to bservation and triangulation. The results of this research is student field practicehavethe ability and skill in using the media to implement the learning, in spite of the media used simple. The problems in the use of media in school practice is a)a short learning period, b) student field practice in comprehensi on factor in using the media, c) the electricity has not reached the classroom, d) lack of understanding of students field practice in using the media and e) classroom managementnot good, not supportfor the use of instructional media.